Method for metallizing carbon fiber board surface

By adopting silk-print conductive silver paste, cleaning, activation and other steps on the surface of carbon fiber board, combined with electrochemical plating and electroplating technology, the problems of uneven thickness and poor binding force are solved, and a dense and smooth, uniform thickness and salt, alkali and acid resistance are achieved, which is suitable for industrial production.

CN116240531BActive Publication Date: 2025-04-29HUIZHOU ONTAP SURFACE TREATMENT TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310229139.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-09
Publication Date
2025-04-29
Estimated Expiration
2043-03-09

AI Technical Summary

Technical Problem

The existing surface metallization method of carbon fiber boards has problems such as uneven coating thickness, poor bonding force, and uneven current distribution during electroplating, which is difficult to meet the requirements of industrial mass production.

Method used

The steps of screen-printed conductive silver paste, cleaning, activation, pre-nickel plating, electrolytic nickel plating, electrolytic nickel plating, electrolytic nickel plating, and electrolytic nickel plating are adopted to form a dense, smooth, uniform thickness and good bonding force by adjusting the particle size of the conductive silver paste, the number of wire mesh mesh, processing temperature and current density.

Benefits of technology

The surface of carbon fiber board is formed into a dense and smooth metal plating layer with uniform thickness and good bonding force, which improves the salt, alkali and acid resistance of the plating, and is suitable for industrial mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116240531B_ABST
    Figure CN116240531B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of carbon fiber surface treatment, and discloses a method for metallizing the surface of a carbon fiber plate, comprising the following steps: screen printing a conductive paste on a carbon fiber plate to obtain a screen-printed carbon fiber plate; cleaning the screen-printed carbon fiber plate to obtain a cleaned carbon fiber plate; activating the cleaned carbon fiber plate to obtain an activated carbon fiber plate; pre-nickel plating the activated carbon fiber plate to obtain a pre-nickel-plated carbon fiber plate; chemically plating the pre-nickel-plated carbon fiber plate to obtain a chemically plated carbon fiber plate; electroplating the chemically plated carbon fiber plate with coke copper to obtain a coke copper-plated carbon fiber plate; electroplating the coke copper-plated carbon fiber plate with ammonia nickel to obtain an ammonia nickel-plated carbon fiber plate. The method can form a dense and smooth metal coating on the surface of the treated carbon fiber plate, which has uniform thickness, good bonding strength, and is resistant to salt, alkali, and acid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of carbon fiber surface treatment, in particular to a method for metallizing the surface of a carbon fiber plate. Background Art

[0002] Carbon fiber is an inorganic polymer fiber with a carbon content of more than 90%, a new material with excellent mechanical properties. Carbon fiber has many excellent properties that many materials cannot match: 1. The specific gravity is less than 1 / 4 of steel, but the strength is ten times higher than that of steel, and it has high specific strength and high specific modulus; 2. Good fatigue resistance, excellent wear resistance, self-lubrication and good damping performance; 3. Good chemical stability, no combustion, no corrosion by acid, alkali and solvent; 4. Small linear expansion coefficient and good dimensional stability; 5. Good heat resistance, and the mechanical properties are slightly reduced at high temperature; 6. Electrical conductivity; 7. Flexibility and weavability. Carbon fiber has the characteristics of high specific strength, high specific modulus, high temperature resistance, corrosion resistance, heat transfer, small thermal expansion coefficient and electrical conductivity due to its special morphology and structure. After the surface of carbon fiber is metallized, it can not only solve the problems of low content of polar groups on the surface of carbon fiber, low surface energy, poor adhesion to the matrix, and more interface defects, but also significantly improve the electrical conductivity of carbon fiber, which can be used for conductive materials and electromagnetic shielding materials.

[0003] At present, there are two main methods for metallization of carbon fiber boards: chemical plating and electroplating. Chemical plating is to reduce metal cations in carbon fiber boards to metal atoms by chemical methods and deposit them on the surface of carbon fiber boards. This method can obtain a copper plating layer with uniform thickness and good bonding strength on the surface of carbon fiber boards, but chemical plating is not as fast as electroplating deposition speed, chemical reaction and process are more complicated, and the stability of coating quality is difficult to guarantee, which is not suitable for industrial mass production. Electroplating is a process for processing the surface of carbon fiber boards by electrolysis. During electrolysis, the carbon fiber board is used as the cathode, and the metal ions in the plating solution are deposited on the surface of the carbon fiber board under the action of direct current to form a dense metal coating. Compared with chemical plating, this method has the advantages of faster electroplating rate, simpler reaction and process, and better coating quality stability, and is more suitable for industrial mass production. However, the surface of the carbon fiber board without surface treatment is hydrophobic, and the current distribution at different positions of the carbon fiber board is uneven. The area first plated with metal ions will shield the area not plated with metal ions, so that the metal coating obtained by electroplating is not smooth enough, the thickness is uneven, and the bonding strength between the metal coating and the carbon fiber is poor. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for metallizing the surface of a carbon fiber plate, which can form a dense and smooth metal coating with uniform thickness and good bonding strength on the surface of the carbon fiber plate after treatment.

[0005] The objective of the present invention is achieved through the following technical solutions:

[0006] A method for metallizing the surface of a carbon fiber plate comprises the following steps:

[0007] (1) Screen printing a conductive paste on a carbon fiber board to obtain a screen printed carbon fiber board.

[0008] In step (1), the screen printing process uses a conductive silver paste with a particle size of 1 to 5 um and a screen with a mesh size of 300 to 400 as the base; the carbon fiber board after screen printing is also baked, and the baking temperature is 120 to 150° C. and the time is 20 to 30 minutes.

[0009] Through experiments, the inventors found that the silk-screen printing treatment specified in the present invention can improve the wettability and current uniformity of the carbon fiber surface, thereby improving the thickness uniformity and bonding strength of the coating of the treated carbon fiber plate.

[0010] (2) Cleaning the carbon fiber plate after silk screen printing to obtain a cleaned carbon fiber plate.

[0011] In step (2), the cleaning treatment is to immerse the screen-printed carbon fiber plate in an alkaline cleaning agent with a concentration of 50 to 80 g / L for cleaning. The alkaline cleaning agent includes sodium hydroxide and trisodium phosphate. The cleaning temperature is 50 to 60° C. and the time is 2 to 5 minutes.

[0012] (3) Activating the cleaned carbon fiber board to obtain an activated carbon fiber board.

[0013] In step (3), the activation treatment is to place the cleaned carbon fiber plate in a sulfuric acid solution with a concentration of 10% to 20% for activation. The temperature of the activation treatment is room temperature and the time is 20 to 60 seconds.

[0014] Through experiments, the inventors found that the activation treatment specified in the present invention can improve the wettability and roughness of the carbon fiber surface, thereby improving the thickness uniformity and bonding strength of the coating of the treated carbon fiber plate.

[0015] (4) Pre-nickel-plating the activated carbon fiber plate to obtain a pre-nickel-plated carbon fiber plate.

[0016] In step (4), the pre-nickel plating treatment is to place the activated carbon fiber plate in a pre-nickel plating solution for pre-nickel plating, wherein the pre-nickel plating solution includes components of the following concentrations: 60-150 ml / L of hydrochloric acid and 150-320 g / L of nickel chloride, the pre-nickel plating treatment temperature is room temperature, the time is 20-60 s, and the current density is 2-5 ASD.

[0017] (5) chemically nickel-plating the pre-nickel-plated carbon fiber sheet to obtain a chemically plated carbon fiber sheet.

[0018] In step (5), the chemical nickel plating treatment is to place the pre-nickel-plated carbon fiber plate in a nickel-phosphorus solution for chemical nickel plating. The nickel-phosphorus solution includes the following components in concentrations: 20-30 g / L nickel sulfate and 25-35 g / L sodium hypophosphite, such as the 3429 series high-phosphorus chemical nickel solution of Huizhou Antongli Technology Co., Ltd. or the 3867 series medium-phosphorus chemical nickel solution of Huizhou Antongli Technology Co., Ltd. 2+ The concentration is 6-7 g / L, and the pH is 4.4-5.2. The temperature of the chemical nickel plating treatment is 85-90° C., and the time is 300-400 seconds.

[0019] Through experiments, the inventors found that through the chemical nickel plating treatment specified in the present invention, by using the chemical nickel plating layer as the bottom layer of the composite coating, the density of the composite coating can be improved, thereby improving the salt, alkali and acid resistance of the composite coating.

[0020] (6) Electroplating the carbon fiber plate after chemical plating with charred copper to obtain a carbon fiber plate after charred copper plating.

[0021] In step (6), the electroplating copper plating treatment is to place the chemically plated carbon fiber plate in a copper plating solution for copper plating, wherein the copper plating solution includes the following components in concentrations: copper pyrophosphate 75-85 g / L and potassium pyrophosphate 320-340 g / L, and a pH of 8.0-8.8. The temperature of the electroplating copper plating treatment is 45-55°C, the time is 180-240s, and the current density is 2-5ASD.

[0022] Through experiments, the inventors found that after the electroplating copper treatment specified in the present invention, the electroplated copper layer is used as an intermediate layer between the chemical nickel plating layer and the electroplated ammonia nickel layer, the density of the composite coating can be improved, thereby improving the salt, alkali and acid resistance of the composite coating.

[0023] (7) Electroplating the carbon fiber plate after electroplating with charred copper with ammonia nickel to obtain a carbon fiber plate after electroplating with ammonia nickel.

[0024] In step (7), the ammonia nickel electroplating treatment is to place the carbon fiber plate after electroplating with charred copper in an ammonia nickel solution for electroplating with ammonia nickel, wherein the ammonia nickel solution comprises the following components in concentrations: 380-420 g / L of nickel sulfamate, 10-20 g / L of nickel chloride and 30-40 g / L of boric acid, with a pH of 4.4-5.2, and the temperature of the ammonia nickel electroplating treatment is 50-60°C, the time is 300-400 s, and the current density is 2-5 ASD.

[0025] (8) The carbon fiber plate after the ammonia nickel electroplating is exposed and developed to obtain a carbon fiber plate after exposure and development.

[0026] (9) Deplating the carbon fiber board after exposure and development to obtain a deplated carbon fiber board.

[0027] In step (9), the stripping treatment is to place the carbon fiber board after exposure and development in a sulfuric acid solution with a concentration of 30% to 60% for stripping. The temperature of the stripping treatment is room temperature and the time is 5 to 10 minutes.

[0028] (10) De-plating the de-plated carbon fiber board to obtain a de-plated carbon fiber board. Drying the de-plated carbon fiber board to obtain a conductive carbon fiber board, wherein the conductive carbon fiber board has a plated pattern area (with conductivity) and a non-pattern area (without conductivity) on its surface.

[0029] In step (10), the stripping treatment is to place the stripped carbon fiber plate in a stripping solution for stripping, and the stripping treatment temperature is room temperature and the time is 2 to 6 minutes.

[0030] Through experiments, the inventors found that through the steps (1) to (7) specified in the present invention and the conditions such as the conductive silver paste particle size, screen mesh number, treatment pH, treatment current density, treatment temperature, and treatment time in each step, a dense, smooth, uniformly thick, well-bonded, salt-resistant, alkali-resistant, and acid-resistant metal coating can be formed on the surface of the carbon fiber board after treatment.

[0031] Compared with the prior art, the present invention has at least the following advantages:

[0032] The method of the present invention can improve the wettability, roughness and current uniformity of the surface of the carbon fiber board through the specified steps (1) to (7) and the conditions of the conductive silver paste particle size, screen mesh number, treatment pH, treatment current density, treatment temperature, treatment time and the like in each step, and can form a dense and smooth metal coating with uniform thickness, good bonding force and resistance to salt, alkali and acid on the surface of the carbon fiber board after treatment. Combined with steps (8) to (10), a special material with both properties can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0034] Figure 1 The present invention is a flowchart of a method for metallizing the surface of a carbon fiber board according to an embodiment of the present invention. DETAILED DESCRIPTION

[0035] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.

[0036] Example 1

[0037] A method for metallizing the surface of a carbon fiber plate comprises the following steps:

[0038] (1) Screen printing a conductive paste on a carbon fiber board to obtain a screen printed carbon fiber board.

[0039] In step (1), the screen printing process uses a conductive silver paste with a particle size of 1 um and a screen with a mesh size of 400 as the base; the carbon fiber board after screen printing is also baked, and the baking temperature is 120°C.

[0040] (2) Cleaning the carbon fiber plate after silk screen printing to obtain a cleaned carbon fiber plate.

[0041] In step (2), the cleaning treatment is to immerse the screen-printed carbon fiber plate in an alkaline cleaning agent with a concentration of 50 g / L for cleaning. The alkaline cleaning agent includes sodium hydroxide and trisodium phosphate. The cleaning treatment temperature is 50° C. and the time is 5 minutes.

[0042] (3) Activating the cleaned carbon fiber board to obtain an activated carbon fiber board.

[0043] In step (3), the activation treatment is to place the cleaned carbon fiber plate in a sulfuric acid solution with a mass concentration of 10% for activation. The temperature of the activation treatment is 20° C. and the time is 60 seconds.

[0044] (4) Pre-nickel-plating the activated carbon fiber plate to obtain a pre-nickel-plated carbon fiber plate.

[0045] In step (4), the pre-nickel plating treatment is to place the activated carbon fiber plate in a pre-nickel plating solution for pre-nickel plating, wherein the pre-nickel plating solution includes components of the following concentrations: 60 ml / L hydrochloric acid and 150 g / L nickel chloride, and the pre-nickel plating treatment temperature is 20°C, the time is 60s, and the current density is 2ASD.

[0046] (5) chemically nickel-plating the pre-nickel-plated carbon fiber sheet to obtain a chemically plated carbon fiber sheet.

[0047] In step (5), the chemical nickel plating treatment is to place the pre-nickel-plated carbon fiber plate in a nickel-phosphorus solution for chemical nickel plating, wherein the nickel-phosphorus solution is a 3429 series high-phosphorus chemical nickel solution of Huizhou Antongli Technology Co., Ltd., and the nickel-phosphorus solution contains Ni 2+ The concentration is 6 g / L, the pH is 4.4, the temperature of the chemical nickel plating treatment is 85° C., and the time is 400 s.

[0048] (6) Electroplating the carbon fiber plate after chemical plating with charred copper to obtain a carbon fiber plate after charred copper plating.

[0049] In step (6), the electroplating copper plating treatment is to place the chemically plated carbon fiber board in a copper plating solution for copper plating, wherein the copper plating solution includes the following components in concentrations: 75 g / L copper pyrophosphate and 320 g / L potassium pyrophosphate, and the pH is 8.0. The temperature of the electroplating copper plating treatment is 45°C, the current density is 2ASD, and the time is 240s.

[0050] (7) Electroplating the carbon fiber plate after electroplating with charred copper with ammonia nickel to obtain a carbon fiber plate after electroplating with ammonia nickel.

[0051] In step (7), the ammonia nickel electroplating treatment is to place the carbon fiber plate after electroplating with charred copper in an ammonia nickel solution for electroplating with ammonia nickel, wherein the ammonia nickel solution comprises the following components in concentrations: 380 g / L nickel sulfamate, 10 g / L nickel chloride and 30 g / L boric acid, with a pH of 4.4, and the temperature of the ammonia nickel electroplating treatment is 50°C, the current density is 2ASD, and the time is 400s.

[0052] Example 2

[0053] A method for metallizing the surface of a carbon fiber plate comprises the following steps:

[0054] (1) Screen printing a conductive paste on a carbon fiber board to obtain a screen printed carbon fiber board.

[0055] In step (1), the screen printing process uses a conductive silver paste with a particle size of 5 um and a screen with a mesh size of 300 as the base; the carbon fiber board after screen printing is also baked, and the baking temperature is 150° C. and the time is 20 minutes.

[0056] (2) Cleaning the carbon fiber plate after silk screen printing to obtain a cleaned carbon fiber plate.

[0057] In step (2), the cleaning treatment is to immerse the screen-printed carbon fiber plate in an alkaline cleaning agent with a concentration of 80 g / L for cleaning. The alkaline cleaning agent includes sodium hydroxide and trisodium phosphate. The cleaning treatment temperature is 60° C. and the time is 2 minutes.

[0058] (3) Activating the cleaned carbon fiber board to obtain an activated carbon fiber board.

[0059] In step (3), the activation treatment is to place the cleaned carbon fiber plate in a sulfuric acid solution with a mass concentration of 20% for activation. The temperature of the activation treatment is 40° C. and the time is 20 seconds.

[0060] (4) Pre-nickel-plating the activated carbon fiber plate to obtain a pre-nickel-plated carbon fiber plate.

[0061] In step (4), the pre-nickel plating treatment is to place the activated carbon fiber plate in a pre-nickel plating solution for pre-nickel plating, wherein the pre-nickel plating solution includes components of the following concentrations: 150 ml / L hydrochloric acid and 320 g / L nickel chloride, and the pre-nickel plating treatment temperature is 40°C, the time is 20s, and the current density is 5ASD.

[0062] (5) chemically nickel-plating the pre-nickel-plated carbon fiber sheet to obtain a chemically plated carbon fiber sheet.

[0063] In step (5), the chemical nickel plating treatment is to place the pre-nickel-plated carbon fiber plate in a nickel-phosphorus solution for chemical nickel plating, wherein the nickel-phosphorus solution is a 3867 series medium-phosphorus chemical nickel solution of Huizhou Antongli Technology Co., Ltd., wherein Ni 2+ The concentration is 7 g / L, the pH is 5.2, the temperature of the chemical nickel plating treatment is 90° C., and the time is 300 s.

[0064] (6) Electroplating the carbon fiber plate after chemical plating with charred copper to obtain a carbon fiber plate after charred copper plating.

[0065] In step (6), the electroplating copper plating treatment is to place the chemically plated carbon fiber board in a copper plating solution for copper plating, wherein the copper plating solution includes the following components in concentrations: 85 g / L copper pyrophosphate and 340 g / L potassium pyrophosphate, and the pH is 8.8. The temperature of the electroplating copper plating treatment is 55°C, the current density is 5ASD, and the time is 180s.

[0066] (7) Electroplating the carbon fiber plate after electroplating with charred copper with ammonia nickel to obtain a carbon fiber plate after electroplating with ammonia nickel.

[0067] In step (7), the ammonia nickel electroplating treatment is to place the carbon fiber plate after electroplating with charred copper in an ammonia nickel solution for electroplating with ammonia nickel, wherein the ammonia nickel solution comprises the following components in concentrations: 420 g / L nickel sulfamate, 20 g / L nickel chloride and 40 g / L boric acid, with a pH of 5.2, and the temperature of the ammonia nickel electroplating treatment is 60°C, the current density is 5ASD, and the time is 300s.

[0068] Example 3

[0069] A method for metallizing the surface of a carbon fiber plate comprises the following steps:

[0070] (1) Screen printing a conductive paste on a carbon fiber board to obtain a screen printed carbon fiber board.

[0071] In step (1), the screen printing process uses a conductive silver paste with a particle size of 3um and a screen with a mesh size of 350 as the base; the carbon fiber board after screen printing is also baked, and the baking temperature is 135°C and the time is 25 minutes.

[0072] (2) Cleaning the carbon fiber plate after silk screen printing to obtain a cleaned carbon fiber plate.

[0073] In step (2), the cleaning treatment is to immerse the screen-printed carbon fiber plate in an alkaline cleaning agent with a concentration of 65g / L for cleaning. The alkaline cleaning agent includes sodium hydroxide and trisodium phosphate. The cleaning treatment temperature is 55°C and the time is 3.5 minutes.

[0074] (3) Activating the cleaned carbon fiber board to obtain an activated carbon fiber board.

[0075] In step (3), the activation treatment is to place the cleaned carbon fiber plate in a sulfuric acid solution with a mass concentration of 15% for activation. The temperature of the activation treatment is 30° C. and the time is 40 seconds.

[0076] (4) Pre-nickel-plating the activated carbon fiber plate to obtain a pre-nickel-plated carbon fiber plate.

[0077] In step (4), the pre-nickel plating treatment is to place the activated carbon fiber plate in a pre-nickel plating solution for pre-nickel plating, wherein the pre-nickel plating solution includes components of the following concentrations: 105 ml / L hydrochloric acid and 235 g / L nickel chloride, and the pre-nickel plating treatment temperature is 30°C, the time is 40s, and the current density is 3.5ASD.

[0078] (5) chemically nickel-plating the pre-nickel-plated carbon fiber sheet to obtain a chemically plated carbon fiber sheet.

[0079] In step (5), the chemical nickel plating treatment is to place the pre-nickel-plated carbon fiber plate in a nickel-phosphorus solution for chemical nickel plating, wherein the nickel-phosphorus solution is a mixture of a 3429 series high-phosphorus chemical nickel solution of Huizhou Antongli Technology Co., Ltd. and a 3867 series medium-phosphorus chemical nickel solution of Huizhou Antongli Technology Co., Ltd. in a mass ratio of 1:1, wherein Ni 2+ The concentration is 6.5 g / L, the pH is 4.8, the temperature of the chemical nickel plating treatment is 88° C., and the time is 350 s.

[0080] (6) Electroplating the carbon fiber plate after chemical plating with charred copper to obtain a carbon fiber plate after charred copper plating.

[0081] In step (6), the electroplating copper plating treatment is to place the chemically plated carbon fiber plate in a copper plating solution for copper plating, wherein the copper plating solution includes the following components in concentrations: 80 g / L copper pyrophosphate and 330 g / L potassium pyrophosphate, with a pH of 8.4, and the temperature of the electroplating copper plating treatment is 50°C, the current density is 3.5 ASD, and the time is 210 s.

[0082] (7) Electroplating the carbon fiber plate after electroplating with charred copper with ammonia nickel to obtain a carbon fiber plate after electroplating with ammonia nickel.

[0083] In step (7), the electroplating of ammonia nickel is to place the carbon fiber plate after electroplating of copper in an ammonia nickel solution for electroplating of ammonia nickel, wherein the ammonia nickel solution comprises the following components in concentrations: 400 g / L nickel sulfamate, 15 g / L nickel chloride and 35 g / L boric acid, with a pH of 4.8. The electroplating temperature of the ammonia nickel is 55°C, the current density is 3.5 ASD, and the time is 350 s.

[0084] Example 4

[0085] The method is basically the same as Example 3, except that it also includes the following steps:

[0086] (8) The carbon fiber plate after the ammonia nickel electroplating is exposed and developed to obtain a carbon fiber plate after exposure and development.

[0087] (9) Deplating the carbon fiber board after exposure and development to obtain a deplated carbon fiber board.

[0088] In step (9), the stripping treatment is to place the exposed and developed carbon fiber board in a sulfuric acid solution with a mass concentration of 45% for stripping. The temperature of the stripping treatment is 30° C. and the time is 7.5 minutes.

[0089] (10) De-plating the de-plated carbon fiber board to obtain a de-plated carbon fiber board. Drying the de-plated carbon fiber board to obtain a conductive carbon fiber board, wherein the conductive carbon fiber board has a plated pattern area (with conductivity) and a non-pattern area (without conductivity) on its surface.

[0090] In step (10), the stripping treatment is to place the stripped carbon fiber plate in a stripping solution (type: Guangshengyuan GSY-003 degreasing agent) for stripping, and the stripping treatment temperature is 30° C. and the time is 4 minutes.

[0091] Comparative Example 1

[0092] It is basically the same as Example 3, except that:

[0093] In step (1), the screen printing process uses a conductive silver paste with a particle size of 8 um and a screen with a mesh size of 200 as the base; the carbon fiber board after screen printing is also baked, and the baking temperature is 100° C. and the time is 40 minutes.

[0094] In step (2), the cleaning treatment temperature is 40° C. and the time is 8 minutes.

[0095] In step (3), the activation treatment is carried out at a temperature of 10° C. and for a time of 100 s.

[0096] In step (4), the temperature of the pre-nickel plating treatment is 10° C., the time is 100 s, and the current density is 1 ASD.

[0097] In step (5), the pH is 3.4. The temperature of the chemical nickel plating treatment is 75° C. and the time is 500 s.

[0098] In step (6), the pH is 7.0, the temperature of the electroplating copper treatment is 35° C., the time is 340 s, and the current density is 1 ASD.

[0099] In step (7), the pH is 3.4, the temperature of the ammonia nickel electroplating treatment is 40° C., the time is 500 s, and the current density is 1 ASD.

[0100] Comparative Example 2

[0101] It is basically the same as Example 3, except that:

[0102] In step (1), the screen printing process uses a conductive silver paste with a particle size of 10 um and a screen with a mesh size of 500 as the base; the carbon fiber board after screen printing is also baked, and the baking temperature is 180° C. and the time is 10 minutes.

[0103] In step (2), the cleaning treatment temperature is 70° C. and the time is 1 min.

[0104] In step (3), the activation treatment is carried out at a temperature of 50° C. and for a time of 10 seconds.

[0105] In step (4), the temperature of the pre-nickel plating treatment is 50° C., the time is 10 s, and the current density is 6 ASD.

[0106] In step (5), the pH is 6.2. The temperature of the chemical nickel plating treatment is 100° C. and the time is 200 s.

[0107] In step (6), the pH is 9.8, the temperature of the electroplating copper treatment is 65° C., the time is 80 s, and the current density is 6 ASD.

[0108] In step (7), the pH is 6.2, the temperature of the ammonia nickel electroplating treatment is 70° C., the time is 200 s, and the current density is 6 ASD.

[0109] Comparative Example 3

[0110] It is basically the same as Example 3, except that: there is no step (1) silk screen processing.

[0111] Comparative Example 4

[0112] It is basically the same as Example 3, except that there is no step (3) activation treatment.

[0113] Comparative Example 5

[0114] The method is basically the same as Example 3, except that: there is no step (5) chemical nickel plating.

[0115] Comparative Example 6

[0116] The method is basically the same as Example 3, except that: there is no step (6) electroplating copper treatment.

[0117] The performance tests were performed on the carbon fiber board samples treated by Examples 1 to 4 and Comparative Examples 1 to 6, wherein the test results of Examples 1 to 4 are shown in Table 1.

[0118] Table 1 Test table of samples of Examples 1 to 4

[0119]

[0120] After experimental testing, the coating of the carbon fiber plate samples treated in Examples 1 to 4 is dense and smooth, uniform in thickness, has good bonding strength, and is resistant to salt, alkali, and acid. It can also significantly improve the conductivity of the carbon fiber. At the same time, the conductive carbon fiber plate of Example 4 is a special material with both properties.

[0121] In terms of data comparison: the bonding strength (ASTM grade) of the coating of the carbon fiber board samples treated in Examples 1 to 4 is 5B. Comparative Examples 1 to 2 changed the conductive silver paste particle size, screen mesh number, treatment pH, treatment current density, treatment temperature, treatment time and other conditions, resulting in the bonding strength of the coating of the carbon fiber board samples treated in Comparative Examples 1 to 2 being 4B, and the appearance and thickness uniformity of the coating are lower than those in Example 3. Comparative Example 3 has no silk screen treatment, resulting in the bonding strength of the coating of the carbon fiber board sample treated in Comparative Example 3 being 4B, which is significantly lower than that in Example 3. This is because the silk screen treatment can improve the wettability and current uniformity of the carbon fiber surface, thereby improving the bonding strength of the coating. Comparative Example 4 has no activation treatment, resulting in the bonding strength of the coating of the carbon fiber board sample treated in Comparative Example 4 being 3B, which is significantly lower than that in Example 3. This is because the activation treatment can improve the wettability and roughness of the carbon fiber surface, thereby improving the bonding strength of the coating. The salt spray, sweat alkali, and sweat acid tests of the coating of the carbon fiber plate sample after the treatment of Comparative Example 5 (no chemical nickel plating treatment) failed. From the comparison of the performance parameters of Example 3 and Comparative Example 5, it can be seen that the lack of a chemical nickel plating layer as the bottom layer of the composite coating will affect the compactness of the composite coating, thereby affecting the salt, alkali, and acid resistance of the composite coating. The salt spray, sweat alkali, and sweat acid tests of the coating of the carbon fiber plate sample after the treatment of Comparative Example 6 (no electroplated coke copper treatment) failed. From the comparison of the performance parameters of Example 3 and Comparative Example 6, it can be seen that by using the electroplated coke copper layer as the intermediate layer between the chemical nickel plating layer and the electroplated ammonia nickel layer, the compactness of the composite coating can be improved, thereby improving the salt, alkali, and acid resistance of the composite coating.

[0122] Experiments have proved that the effect of the present invention can be achieved only by the steps specified in the present invention and the conditions such as the conductive silver paste particle size, screen mesh number, treatment pH, treatment current density, treatment temperature, and treatment time in each step, and a dense, smooth, uniformly thick, well-bonded, and salt-resistant, alkali-resistant, and acid-resistant metal coating can be formed on the surface of the carbon fiber board after treatment.

[0123] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for metallizing the surface of a carbon fiber plate, characterized in that: The method comprises the following steps: (1) screen printing a conductive paste on a carbon fiber plate to obtain a screen printed carbon fiber plate; (2) cleaning the carbon fiber plate after silk screen printing to obtain a cleaned carbon fiber plate; (3) activating the cleaned carbon fiber plate to obtain an activated carbon fiber plate; (4) pre-nickel-plating the activated carbon fiber plate to obtain a pre-nickel-plated carbon fiber plate; (5) performing chemical nickel plating on the pre-nickel-plated carbon fiber plate to obtain a chemically plated carbon fiber plate; (6) electroplating the carbon fiber plate after chemical plating with charred copper to obtain a carbon fiber plate after charred copper plating; (7) electroplating the carbon fiber plate after the copper electroplating with ammonia nickel to obtain the carbon fiber plate after the ammonia nickel electroplating; (8) exposing and developing the carbon fiber plate after the ammonia nickel electroplating to obtain the carbon fiber plate after exposure and development; (9) stripping the carbon fiber sheet after exposure and development to obtain a stripped carbon fiber sheet; (10) stripping the carbon fiber plate after stripping to obtain a stripped carbon fiber plate; In step (1), the screen printing process uses a conductive silver paste with a particle size of 1 to 5 um and a screen with a mesh size of 300 to 400 as the base; the screen-printed carbon fiber board is baked at a temperature of 120 to 150° C. In step (2), the cleaning treatment is to place the screen-printed carbon fiber plate in an alkaline cleaning agent with a concentration of 50 to 80 g / L for immersion cleaning, wherein the alkaline cleaning agent includes sodium hydroxide and trisodium phosphate, and the cleaning treatment temperature is 50 to 60° C.; In step (3), the activation treatment is to place the cleaned carbon fiber plate in a sulfuric acid solution with a concentration of 10% to 20% for activation, and the temperature of the activation treatment is room temperature; In step (4), the pre-nickel plating treatment is to place the activated carbon fiber plate in a pre-nickel plating solution for pre-nickel plating, wherein the pre-nickel plating solution comprises components of the following concentrations: 60-150 ml / L of hydrochloric acid and 150-320 g / L of nickel chloride, the pre-nickel plating treatment temperature is room temperature, and the current density is 2-5 ASD; In step (5), the chemical nickel plating treatment is to place the pre-nickel-plated carbon fiber plate in a nickel-phosphorus solution for chemical nickel plating. 2+ The concentration is 6-7 g / L, the pH is 4.4-5.2, and the temperature of the chemical nickel plating treatment is 85-90°C; In step (6), the electroplating copper treatment is to place the chemically plated carbon fiber plate in a copper solution for copper electroplating, wherein the copper solution comprises the following components in concentrations: 75-85 g / L copper pyrophosphate and 320-340 g / L potassium pyrophosphate, and a pH of 8.0-8.

8. The temperature of the electroplating copper treatment is 45-55° C., and the current density is 2-5 ASD. In step (7), the electroplating of ammonia nickel is to place the carbon fiber plate after electroplating of charred copper in an ammonia nickel solution for electroplating of ammonia nickel, wherein the ammonia nickel solution comprises the following components in concentrations: 380-420 g / L of nickel sulfamate, 10-20 g / L of nickel chloride and 30-40 g / L of boric acid, with a pH of 4.4-5.2, and the temperature of the electroplating of ammonia nickel is 50-60° C., and the current density is 2-5 ASD; In step (9), the stripping treatment is to place the carbon fiber plate after exposure and development in a sulfuric acid solution with a concentration of 30% to 60% for stripping, and the temperature of the stripping treatment is room temperature; In step (10), the stripping treatment is to place the stripped carbon fiber plate in a stripping solution for stripping, and the temperature of the stripping treatment is room temperature.

Citation Information

Patent Citations

  • Electroplating method for improving surface hardness of carbon fibers

    CN116716641A